Literasi Budaya Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Lakidende - Anas (FKIP, Universitas Lakidende Unaaha, 2022)
This study aims to examine the role and impact of cultural literacy learning for students of the Faculty of Teacher Training and Education. This research used a qualitative approach with a descriptive method. The data collection was carried out through observation, in-depth interviews, and documentation on 23 students and 2 lecturers as the informants. Validation and reliability of the collected data were conducted by data reduction, display data, and data verification. The results suggested that encouraging cultural literacy offering Tolaki Educational, Language, and Cultural Literacy course have impacted on the knowledge of FKIP students of Lakidende University about Tolaki culture. This not only became knowledge but also became a means to maintain culture through writing student final assignments.